25(OH)D(3) and Cardiovascular Risk Factors in Female Nonhuman Primates - Jorgensen, Matthew J. (Mary Ann Liebert, Inc., 2012)
OBJECTIVE: To determine if interindividual differences in plasma concentrations of 25-hydroxyvitamin D(3) (25(OH)D(3)) have pathophysiologic significance, we evaluated a cohort of female monkeys, seeking to identify associations with clinically relevant cardiovascular risk factors, including age, abdominal obesity (waist circumference), and high-density lipoprotein cholesterol (HDL-C). METHODS: One hundred fifty-five female vervet monkeys (Chlorocebus aethiops sabaeus) aged 3–25 years consumed a typical western diet for 7–8 weeks that provided a woman's equivalent of approximately 1000 IU/day of vitamin D(3). Measurements of vitamin D(3) and HDL-C concentrations, as well as waist circumference, were obtained. RESULTS: Among young monkeys (aged 3–5 years), compared to older monkeys (aged 16–25 years), the mean plasma 25(OH)D(3) concentrations were 82.3±3.2 ng/mL and 58.6±2.9 ng/mL (p<0.0001), respectively. Plasma 25(OH)D(3) concentrations had a range of 19.6–142.0 ng/mL (mean±standard error [SE] 66.4±1.7 ng/mL). 25(OH)D(3) concentrations were inversely associated with age (p<0.0001) and waist circumference (p=0.016) and were positively correlated with HDL-C (p=0.01). However, when statistically controlling for age, none of these relationships remained significant. CONCLUSIONS: Higher plasma concentrations of 25(OH)D(3) were associated with more favorable cardiovascular risk factors, with inverse associations observed between 25(OH)D(3) and abdominal obesity, HDL-C, and age. These associations were no longer significant when controlling for age.